Challenging 'one size fits all': Continued use of sprinkler irrigation in a state‐led drip irrigation project in Morocco. (27th January 2022) - Kettani, Abla; Hammani, Ali; Taky, Abdelilah; Kuper, Marcel
Abstract: The current focus on water saving in drip irrigation projects has stifled more classical engineering debates on the relevance of different irrigation techniques for specific field conditions. We show that these debates remain important by analysing a drip irrigation project implemented in a sprinkler irrigation district in north‐west Morocco. The objective is to understand the apparent paradox of a state‐promoted switch to drip irrigation, provided free of charge to farmers who welcomed the project but continued using sprinkler irrigation. Data were gathered during field observations and in interviews with 138 farmers, while secondary data came from the irrigation authority. The results show that most farmers were interested in the drip irrigation project, which solved existing problems of the sprinkler network, including the difficulty of sharing hydrants, high water bills and sharing mobile sprinkler equipment. However, once the project had provided individual water access and customized water bills, 48% of farmers switched totally or partially back to sprinkler irrigation, which they considered better suited to field conditions (soils, crops, irrigation frequency). The implementation of drip irrigation in large‐scale irrigation schemes needs to go beyond the objective of water saving and be adapted to specific natural and socio‐economic conditions. Résumé: La question de l'économie d'eau a marginalisé les débats techniques plus classiques sur la pertinence des différentes techniques d'irrigation pour des conditions de terrain spécifiques. Nous montrons que ces débats restent d'actualité en analysant le projet de reconversion à l'irrigation localisée d'un secteur d'irrigation par aspersion dans le périmètre irrigué du Gharb (Maroc). L'objectif est de comprendre le paradoxe apparent d'une reconversion promue par l'État vers l'irrigation au goutte‐à‐goutte, subventionné à 100% et plébiscité par les agriculteurs, qui continuent pourtant à utiliser l'aspersion. Les données ont été recueillies par des observations de terrain, des entretiens avec 138 agriculteurs et des données obtenu de l'office responsable de la gestion de l'eau du périmètre. Les résultats montrent que l'intérêt des agriculteurs dans le projet est expliqué par le fait qu'il a résolu les problèmes du système d'irrigation collective par aspersion. Une fois que le projet a mis en place des prises et des factures d'eau individuelles, 48% des agriculteurs sont revenus totalement ou partiellement à l'irrigation par aspersion, qui s'est avérée mieux adaptée aux conditions locales. La mise en œuvre de l'irrigation au goutte‐à‐goutte dans les périmètres irrigués à grande échelle doit aller au‐delà de l'objectif d'économie d'eau et être adaptée aux conditions naturelles et socio‐économiques spécifiques.